The Challenge of Setting “Climate Ready” Ecological Targets for Environmental Flow Planning - Judd, Meegan; Bond, Nicholas; Horne, Avril C. (Frontiers in Environmental Science, 2022)
Implementing environmental flows has emerged as a major restoration tool for addressing the impacts of hydrologic alteration in large river systems. The ‘natural flow paradigm’ has been a central guiding principle for determining important ecohydrological relationships. Yet, climate change and associated changes in rainfall run off relationships, seasonality of flows, disruptions to food webs and species life cycle cues mean these existing relationships will, in many circumstances, become obsolete. Revised thinking around setting ecological objectives is required to ensure restoration targets are achievable, particularly in regions where water scarcity is predicted to increase. Through this lens ‘climate ready’ targets are those that are robust to changing water availability or incorporate future adaptation options. Future objective setting should be based around the inclusion of changing climate and water availability, and the associated species and ecosystem vulnerabilities, and expected outcomes under different policy and adaptation options. This paper uses south eastern Australia as a case study region to review the extent to which current water management plans include climate considerations and adaptation in objective setting. Results show untested climate adaptation inclusions, and a general lack of acknowledgement of changing hydrological and ecological conditions in existing management plans. In response this paper presents a process for setting objectives so they can be considered ‘climate ready’.